FAKTOR YANG MEMPENGARUHI WISATAWAN NUSANTARA KE BALI DI MASA PANDEMI COVID-19 - SJ, Ni Wayan Diasputri; Sudana, I Putu; Agus Wikanatha Sagita, Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 1 (2022): Jurnal IPTA (July 2022)DO - 10.24843/IPTA.2022.v10.i01.p05, 2022)
The rapid decline of the tourism sector during the pandemic makes this study important, because it can move the Bali tourism sector by knowing the factors that affect the intention of visiting domestic tourists who have visited Bali during the pandemic. So, it will describe what is desired by tourists such as: green zone areas, attractions that have established health protocols, and destinations that still attract tourists. This research was conducted in Bali especially Tanah Lot Special Tourism Attraction, Double Six Seminyak Beach, Ubud Monkey Forest, using 100 tourists’ samples determined according to slovin formula. Researchers used questionnaires distributed to tourists who had visited Bali. Then the data is analyzed using factor analysis with the help of Statistical Package for the Social Sciens Version 21.0. The results of the study are 1) there are seven factors formed in influencing the intention of visiting Indonesian tourists during the pandemic to Bali. These factors include travel risk factors, destination image factors, driving factors, hospitality risk factors, pull factors, destination risk factors and trust factors. 2) the dominant factor that influences the intention to visit Indonesian tourists during the pandemic to Bali is the first factor named travel risk factor. Travel risk factors outperformed other factors with variance percentage of 37,216% and eigenvalue of 13,770. The indicator of forming factors that have the highest loading factor value on travel risk factors is the nature of traveling with a loading factor of 0.777.